1998
DOI: 10.1021/jf970591l
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric Separation of Dansyl-Derivatized dl-Amino Acids by β-Cyclodextrin-Modified Micellar Electrokinetic Chromatography

Abstract: β-Cyclodextrin (CD)-modified micellar electrokinetic chromatography (MEKC) was applied to enantiomeric separation of Dns (dansyl-derivatized)-dl-amino acids with sodium dodecyl sulfate (SDS). Increase in the pH value and SDS concentration of the background electrolyte (BGE) buffer solution was found to prolong the migration time and improve the resolution (Rs) of Dns-dl-amino acids. Rs of each dl-amino acid was <1.0 when 100 mM SDS/75 mM β-cyclodextrin/250 mM borate (pH 8.3) was utilized as BGE buffer. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Chiral separations of amino acids are generally performed by attaching aromatic moieties to facilitate interaction with CDs [35,36]. In this work, FITC was used as derivatizing agent, which not only improved detection sensitivity but also enhanced chiral separation of the amino acids tested.…”
Section: Chiral Separationmentioning
confidence: 99%
“…Chiral separations of amino acids are generally performed by attaching aromatic moieties to facilitate interaction with CDs [35,36]. In this work, FITC was used as derivatizing agent, which not only improved detection sensitivity but also enhanced chiral separation of the amino acids tested.…”
Section: Chiral Separationmentioning
confidence: 99%
“…CZE has become a powerful and popular separation technique because of its fast separation and high resolution achieved. The advantages of capillary electrophoresis over high-performance liquid chromatography were reported to be high separation efficiency, easy changes of carrier electrolyte media, and nanoliter levels of sample and media [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, quantification of ascorbic acid in foods has been performed by micellar electrokinetic capillary chromatography (MEKC) using sodium dodecyl sulfate or sodium deoxycholate as surfactant [11][12][13]. However, compared with CZE, MEKC suffers the major drawbacks of complex carrier electrolyte preparation as well as long migration time of analytes [7,14,15]. Recently, Choi and Jo [16] demonstrated that CZE was effective in determining L-AA within 2 min using 0.1 M Na-borate (pH 8.0) as carrier electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, racemization of compositional amino acids in alkalitreated duck eggs (Pidan), analyzed by micellar capillary electrophoresis, was found significant. The racemization values for serine, aspartic acid, glutamic acid, and phenylalanine in Pidan albumen alkali-pickled for 20 days were determined to be 41.84%, 35.74%, 19.92%, and 16.44%, respectively (Chang et al, 1998). Friedman et al (1981) and Liener (1994) have pointed out that the factors affecting LAL formation are pH, alkaline-treating time, and heating temperature as well as sources of protein samples.…”
Section: Introductionmentioning
confidence: 99%
“…Micellar capillary electrophoresis, based on the differential partitioning of analytes between the micelle and the surrounding aqueous phase (Terabe et al, 1989(Terabe et al, , 1993, has been reported to be effective in the separation of enantiomers (Ozaki et al, 1995;Tsai et al, 1998). Enantiomeric separation can be achieved by using a chiral environment that interacts with the enantiomers either before or during the separation process, forming stable diastereoisomers or a labile diastereomeric complex, respectively.…”
Section: Introductionmentioning
confidence: 99%